Building supply chain resilience with digitalization - Kim Hua Tan (Asian Development Bank Institute (ADBI), 2023)
How resilient is your supply chain? The fallout from the COVID-19 pandemic laid bare the vulnerability of global supply chains. One of the main business challenges that firms faced was the lack of end-to-end supply chain visibility, which impacts critical operational decisions. If firms are unable to see what is happening in their supply chains, they will not be able to manage them well. In the aftermath of the pandemic, firms have been incorporating the lessons learnt from the pandemic to reconfigure supply chains and increase visibility and responsiveness to withstand future unanticipated disruptions as well as predictable events such as adverse weather or logistics delays. This paper aims to unpack how digitalization can support supply chain resilience and agility. The key questions are: a) What does it take to become more resilient? b) How can digital technologies play a part in providing greater certainty and flexibility to improve supply chain resilience? and c) How should firms go about implementing digital transformation? This paper discusses and explains the various dimensions, phases, and strategies of supply chain resilience. Resilience is understood as a function of a firm's capability to have a conscious awareness of complex interconnected environments and the reconciling capacity to swiftly manage key vulnerabilities. Hence, increased end-to-end visibility of the supply chains using advanced technology and digitalization is vital for firms to pick up early signals of uncertainties, thereby gaining sufficient time to orchestrate operations and resources to withstand disruptions. However, supply chain visibility is not about a collection of digital tools. The research reveals that the building blocks of digitalization capabilities are a triangle of interconnected value levers comprised of a digital workforce, digital backbone, and digital twin. The paper concludes with recommendations for policymakers on how to best help firms realize their digital potential to boost supply chain resilience.
Keywords: M11; 330; digitalization; supply chain resilience; capabilities; responsiveness